La tradizione del ramo italico antico del «Libro dei sette savî» (Carte Romanze, 2022)
The essay examines in a textual-philological perspective the ancient Italian tradition of the Book of the Seven Sages, the one constituted by the versions C (northern), L (latin) and M (venetian), as a first step towards a new critical edition of the three texts.